2022
DOI: 10.3390/v14122626
|View full text |Cite
|
Sign up to set email alerts
|

Rildo: Real-World Multicenter Study on the Effectiveness and Safety of Single-Tablet Regimen of Dolutegravir plus Rilpivirine in Treatment-Experienced People Living with HIV

Abstract: Two-drug regimens (2DRs) are emerging in clinical practice guidelines as treatment option for both naive and treatment-experienced people living with HIV (PLHIV). Objectives: To determine the real-life effectiveness of 2DR with 25 mg RPV plus 50 mg DTG in a single-tablet regimen (RPV/DTGSTR) and its impact on viral and immune status, lipid profile, and inflammatory markers. Methods: This observational study included 291 treatment-experienced PLHIV, starting 2DR with RPV/DTGSTR between 29 January 2019 and 2 Feb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
(30 reference statements)
1
3
0
Order By: Relevance
“…Although sub-optimal adherence cannot be excluded, it is reassuring that the future treatment options for those participants were not compromised. Furthermore, these findings correlate with clinical and real-world trials [6][7][8][23][24][25][26][27][28][29][30][31]33] and show that loss of virological control with DTG-based 2DRs is extremely rare and that the development of resistance to either DTG, 3TC, or RPV is rare. In this sense, our findings are attractive because we can demonstrate high rates of viral suppression despite including long-term diagnosed and pretreated PLWHIV and multimorbidity.…”
Section: Discussionsupporting
confidence: 73%
“…Although sub-optimal adherence cannot be excluded, it is reassuring that the future treatment options for those participants were not compromised. Furthermore, these findings correlate with clinical and real-world trials [6][7][8][23][24][25][26][27][28][29][30][31]33] and show that loss of virological control with DTG-based 2DRs is extremely rare and that the development of resistance to either DTG, 3TC, or RPV is rare. In this sense, our findings are attractive because we can demonstrate high rates of viral suppression despite including long-term diagnosed and pretreated PLWHIV and multimorbidity.…”
Section: Discussionsupporting
confidence: 73%
“…The data obtained in this real-life study confirm that simplification to dual therapy with DTG + 3TC is an effective and safe as alternative to the standard triple therapy in pretreated and virologically stable HIV-infected patients, as shown in several clinical trials and other observational studies [ 14 , 15 , 16 ] along other dual therapies such as atazanavir/ritonavir plus lamivudine [ 5 ], dolutegravir plus boosted darunavir [ 22 ], rilpivirine plus boosted darunavir [ 23 ] or rilpivirne plus dolutegravir [ 19 , 24 ].…”
Section: Discussionmentioning
confidence: 81%
“…A pharmacoeconomic analysis was performed comparing DTG + 3TC therapy versus BIC/TAF/FTC, DRV/c/TAF/FTC and RPV/DTG as the most widely used reference treatments in the current HIV panorama. To perform this analysis, we retrieved data from studies with patients with similar characteristics using the results obtained from this study in mITT patients for DTG + 3TC treatment and those from the systematic review performed by Mazzitelli et al [ 17 ] for BIC/TAF/FTC, the EMERALD study for DRV/c/TAF/FTC [ 18 ] and the recent Rildo Study for RPV/DTG [ 19 ].…”
Section: Individuals and Methodsmentioning
confidence: 99%
“…Furthermore, they explore the effects of these treatments on lipid profiles, providing crucial insights into the potential metabolic implications for HIV patients. Hidalgo-Tenorio et al and Lee et al focused on the efficacy and safety of dual regimens—rilpivirine/dolutegravir and lamivudine/dolutegravir, respectively [ 12 , 13 ]. Hidalgo-Tenorio et al found a very low percentage of virological failure and excellent durability.…”
mentioning
confidence: 99%